Dual‐Functional Photocatalysis: Concurrent Photocatalytic Hydrogen Generation and Dye Degradation Using MIL‐125‐NH2 under Visible Light Irradiation (Adv. Funct. Mater. 52/2018). (27th December 2018) - Kampouri, Stavroula; Nguyen, Tu N.; Spodaryk, Mariana; Palgrave, Robert G.; Züttel, Andreas; Smit, Berend; Stylianou, Kyriakos C.
Abstract : Dual‐functional photocatalytic activity for simultaneous hydrogen (H2 ) generation and degradation of an organic pollutant is achieved under visible‐light irradiation. In article number1806368, Kyriakos C. Stylianou and co‐workers employ a visible‐light responsive metal‐organic framework, MIL‐125‐NH2, with abundant nickel phosphide (Ni2 P) nanoparticles as co‐catalysts. In a single photocatalytic process, H2 is generated in high rates and Rhodamine B is photo‐degraded.